ANALISIS PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MOTOR HEPY CABANG JAWA TENGAH - Murdiyanto, Agus (Jurnal Ilmiah Telaah Manajemen, 2012)
This study aims to analyze the effect of Work Motivation and Work Environment on Employee Performance. This study uses primary data by distributing questionnaires to employees Hapi Motor Branch  of  Central  Java  with  respondents  overall  employee  Motor  Hapy  the  census.  Test  Result Statistics independent sample t-test showed the influence of hypothesis testing work motivation on employee performance can be summed up in partial Work Motivation significant positive effect on employee   performance   variables.   Hypothesis   testing   effect   on   Employee   Performance   Work Environment concluded in partial Workplace significant positive effect on employee performance variables. Results of R Square of 0.76 this means that 76% of variation can be explained by the Employee Performance variation of the two independent variables Work Motivation and Work Environment. While the remaining 24% is explained by reasons - other causes outside the model. Keywords: Work Motivation, Work Environment and Employee Performance